Efektivitas dan Dampak Program Bantuan Kredit Usaha Rakyat (KUR) Terhadap Pendapatan dan Kesempatan Kerja Usaha Mikro Kecil dan Menengah (UMKM) di Kota Denpasar - Putra, I Gusti Agung Alit Semara; Saskara, Idaayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
The economic chaos happened in several countriesin 1997 has its impact to national economic in getting it more unstable. Amidst the national economy crisis, micro and middle business level has been able to keep their existence and is one of the alternatif which is considered to be able touphold national economy both in encouraging national economy growth and employment, but it still get obstacles and constrains. One of constrain is the funding. For micro and middle business, loan is considered to be important enough to meet the needs for financing working capital in running business. In order to tackle those constrains, government launched funding program for UMKM and cooperative, i.e.Loan for Public Business (KUR). Through Loan for Public Business (KUR) aid program given by government, it is expected for those who run the UMKM to keep encouraged in developing their business. The aim of this study is to identify the Effectiveness of Loan for Public Business (KUR) program to Earning and Employment Opportunities of Micro and Medium Business (UMKM) in Denpasar. It used non parametric statistic method of Mc Nemar to identify the Effectiveness of Loan for Public Business (KUR) program to Earning and Employment Opportunities of Micro and Medium Business (UMKM) in Denpasar. Data collected areprimary data from UMKM which get theaid program Loan for Public Business (KUR) 135 people and from that taken sample collected 75 people. The analysis result shows that success rate of KUR aid program showed from indicators i.e. input, process, and output in Denpasar classified as success. It is showed from the average scoreearned fromeach indicator input, process and output. Mc Nemar analysis result showed that KUR aid programhas positive impact to earning and employment opportunities of micro and medium business (UMKM) in Denpasar. Thus it is suggested to government to continue this aid program, but to do recollection of data for UMKM which is about to earn or has earned KUR in order to prevent the abuse of benefits and purpose of giving KUR aid.
Keywords: Effectiveness; KUR; UMKM